'Learning for resilience': Developing community capital through flood action groups in urban flood risk settings with lower social capital. (March 2018) - McEwen, Lindsey; Holmes, Andrew; Quinn, Nevil; Cobbing, Paul
Abstract: The role of civil agency in preparing and adapting to changing risk is an increasingly critical element within devolved local flood risk management. However, effective civil agency for flood resilience needs to draw on, and if necessary develop, community capital. Community Action Groups form one model for local resilience building for flood risk, and one actively supported by some governments. This research evaluates the participatory model of flood group development involving horizontal support rather than top-down or bottom-up generation. The process involved nascent groups working with an NGO facilitator in the implementation of a set of processes framed in the context of 'learning for resilience' that supported flood group development in a situation of challenged social capital (lower socio-economic status; health issues, lack of previous flood experience) in the UK. The methodology involved repeat semi-structured interviews with flood group members and flood risk management (FRM) agencies who worked with them through the process, as well as observation of flood group meetings. Results outline how groups emerge from transient and disconnected communities, the value of local knowledge, evolving communication skills and agency, normalisation of group members within participatory processes, frustrations within these processes, group sustainability and FRM agency perspectives. Discussion then critiques the co-working/partnership model and assesses its implications for social 'learning for resilience' within challenged flood groups with variable social capital. The authors propose a framework ('The 6Ss') for anticipating concerns or barriers within such participatory processes as a guide to future local urban DRR practice.